Knowledge and Perception Regarding Ketogenic Diet Among Students of College of Nursing, Medicine and Applied Medical Sciences at Northern Border University, Arar, KSA - Fatima, Waseem; Naif Alanazi, Danah F.; Alanazi, Norah Badar; Zaidi, Rizwan Fatima; Ansari, Mohd. Imran (Current Nutrition & Food Science, 2023)
Background: The Ketogenic diet has gained popularity, especially among college students in the past few years, mainly as a strategy for fast weight losse, but due to lack of appropriate knowledge of ketogenic diets plans might affect their overall health. Therefore, the present study was designed to evaluate knowledge and perception about ketogenic diet among students of three different faculties of Northern Border University, Arar, KSA. Methods: The present study had a cross sectional study design and a total of 303 (214 female and 89 males) students were contacted between 15 February and 20 March, 2021. A selfadministered online (Google form) questionnaire was used to investigate socio-demographic data as well as student’s knowledge and perception about the ketogenic diet. Results: The majority of the participants, 197 (65%) know that ketogenic diet comprises of high fat, moderate protein, and low carbohydrate. The main therapeutic aim for adopting a ketogenic diet was weight loss for 153 participants (50.3%), whereas 115 (38%) of them adopted it for treating poly cystic ovary (PCOD) and only 84 (27. 7%) for controlling diabetes. The source of knowledge about the ketogenic diet was primarily social media 199 (65.9%), and only 82 (27.2%) adopted it after consultation from a dietitian. However, 72 participants (23.8%) believed that the ketogenic diet did not have any adverse effects on the human body. Conclusion: The result of the present study indicates that students had convincing knowledge and perception about the ketogenic diet as well as its therapeutic uses. However, pre-diet counseling is imperative for everyone to know every aspect and correct technique for carrying out this diet.
Keywords: perception